Functional multi-layer composite fabric and preparation method thereof
The multi-layer composite fabric addresses odor and antioxidant issues by using a cotton fabric structure with a composite fiber membrane and polyurethane silica, achieving effective odor control and radical scavenging through cyclodextrin and nano-anions, with a silica protective film for durability.
Patent Information
- Application Number
- CN202411426111.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-14
AI Technical Summary
Existing textiles lack efficient multi-functional properties for both odor control and antioxidant protection, particularly in high humidity conditions, leading to hygiene issues and skin aging.
A functional multi-layer composite fabric structure comprising cotton fabric, a composite fiber membrane, and a polyurethane silica membrane, where β-cyclodextrin forms an inclusion complex with tert-butylhydroquinone, coated with nano-anion powder, and a polyurethane silica layer is applied under microwave and high-pressure conditions to enhance deodorization and antioxidant capabilities.
The fabric effectively adsorbs and degrades odors while scavenging free radicals, providing strong deodorization and antioxidant properties through cyclodextrin and nano-anions, with the silica layer forming a protective film for enhanced durability.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of multi-layer fabrics, and in particular to a functional multi-layer composite fabric and a preparation method thereof. Background Art
[0002] With the advancement of science and technology and the change of life attitude, people have higher and higher requirements for the performance of clothing products, which are more rational and specific, and are driving textiles to gradually develop in a safe, environmentally friendly, healthy and sustainable composite direction. The skin plays an important role as a protective barrier between the internal and external environment. In daily life, it is often exposed to the external environment, and accompanied by factors such as stress, age, and environmental pollutants. The active oxygen free radicals with strong oxidative properties inside and outside the body will be produced too much or eliminated too slowly and attack cells and tissues, causing human skin aging and diseases. In high temperature, closed, humid, pressure, emotional tension, etc., the human body will inevitably produce odor and appear embarrassing and embarrassing, especially in summer.
[0003] At the same time, my country is gradually experiencing an aging population, and the body odor of the elderly has also begun to become a widely concerned issue. Textiles are a common odor carrier due to their loose and porous structure, and are very easy to absorb odors. Odors absorbed during wearing or use, such as armpit odor, foot odor, and body odor of the elderly, also seriously affect people's physical and mental health, and even have a certain degree of impact on life and health. When the microclimate humidity of the human body or clothing increases, dandruff and sweat will breed bacteria, causing the human body to emit odor and cause hygiene problems.
[0004] Nowadays, textiles with single anti-oxidation or deodorization functions can no longer meet people's demand for efficient functional clothing products, and there are many disadvantages, such as single product function and poor durability. Therefore, it is particularly necessary to invent a functional multi-layer composite fabric. Summary of the invention
[0005] The purpose of the present invention is to provide a functional multi-layer composite fabric and a preparation method thereof, so as to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a functional multi-layer composite fabric, wherein the structure of the functional multi-layer composite fabric is cotton fabric-composite fiber membrane-cotton fabric-polyurethane silica membrane;
[0007] The preparation method of the functional multi-layer composite fabric comprises the following preparation steps:
[0008] (1) Mix β-cyclodextrin and 35 wt% ethanol aqueous solution, heat to 50-70°C, stir at 70-100 rpm for 20-40 min, add tert-butylhydroquinone, heat to 55-80°C, ultrasonicate at 21 kHz for 2-5 h, cool to 2-8°C, let stand for 20-30 h, filter, take the solid, wash with anhydrous ethanol 1-3 times, and dry at 50-80°C for 2-5 h to obtain inclusion compound A;
[0009] (2) Mix the inclusion complex A, nano-anion powder, polyvinyl pyrrolidone and deionized water, stir at 500-1000 rpm for 1-3 hours, add sodium cellulose, continue stirring for 2-4 hours, let stand for 24 hours, and then spin to obtain a composite fiber membrane;
[0010] (3) The composite fiber membrane is compounded between two layers of cotton fabric using a polyurethane adhesive. The weight of the cotton fabric is 130g / m 2 , coating amount is 8~15g / m 2 , polyurethane silica is coated on one side of the cotton fabric, placed in a high pressure environment, and subjected to microwave treatment to obtain a functional multi-layer composite fabric.
[0011] Furthermore, in step (1), the mass ratio of the β-cyclodextrin, 35 wt% ethanol aqueous solution, and tert-butylhydroquinone is 1-2:100:1-2.
[0012] Furthermore, the nano negative ion powder in step (2) is prepared by mixing seaweed charcoal, cerium oxide, manganese dioxide and opal in a mass ratio of 30-50:1-3:5-10:20-50.
[0013] Furthermore, the spinning process parameters of step (2) are: needle diameter of 1 mm, receiving distance of 22 cm, and speed of 50-85 m / min.
[0014] Furthermore, the thickness of the composite fiber membrane in step (2) is 0.2-0.5 mm.
[0015] Furthermore, in step (2), the mass ratio of the inclusion complex A, nano anion powder, polyvinyl pyrrolidone, deionized water, and sodium cellulose is 1:0.5:0.1~0.5:20~30:2~5.
[0016] Furthermore, the thickness of the polyurethane silica in step (3) is 10 μm.
[0017] Furthermore, in the polyurethane silica of step (3), the weight ratio of the aqueous polyurethane resin, nano-silica, cuprous sulfate, KH550 coupling agent, and water is 50-70:8-15:1-9:4-8:80-100.
[0018] Furthermore, the pressure of the high pressure environment in step (4) is 10 MPa.
[0019] Furthermore, the process parameters of the microwave treatment in step (4) are: power of 750-1000 W and time of 1-5 min.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] The fabric structure of the present invention is cotton fabric-composite fiber membrane-cotton fabric-polyurethane silicon dioxide membrane. Tertiary butyl hydroquinone is used to slowly enter the cavity of beta-cyclodextrin macromolecules through the hydrophobic force. As the molecular movement is intensified, the solubility of beta-cyclodextrin gradually increases, and the amount of cyclodextrin in the form of molecules in the solution also increases, which is conducive to hydrogen bonding between tertiary butyl hydroquinone and beta-cyclodextrin to form an inclusion complex and enhance the stability of the matrix. Then, the composite beta-cyclodextrin is coated with nano anion powder, and a micro-convex nano fiber membrane containing anion powder is obtained by spinning. The membrane is placed between two layers of cotton fabrics as an adhesive. The upper and lower cotton fabrics are put together, and under a microwave and high-pressure environment, the micro-protrusions on the surface of the fiber membrane are embedded in the fibers under the force, expanding the fiber gaps and forming adsorption holes. Cyclodextrin and negative ions work together to adsorb and degrade odors, allowing the fabric to achieve a stronger deodorization function. Then, the polyurethane silica coated on the top layer of the fabric penetrates into the fiber gaps under a microwave and high-pressure environment to form a three-dimensional silica protective film. It also forms chemical covalent bonds through the reaction of siloxane with silica particles and hydroxyl groups on cotton fibers, firmly attaching to the cotton fabric, and scavenging free radicals together with tert-butylhydroquinone to enhance the antioxidant properties of the fabric. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the functional multi-layer composite fabrics prepared in the following examples are as follows:
[0024] Antioxidation: The same size of the embodiment and the comparative example were used for antioxidant test using the DPPH method. The ability of the fabric to eliminate free radicals was determined by measuring the absorbance change of the DPPH ethanol solution at 517 nm. The smaller the absorbance, the more free radicals were eliminated, and the better the antioxidant performance.
[0025] Deodorization: Take the same size of the embodiment and the comparative example and refer to GB / T33610.2, and use the ammonia removal rate to evaluate the deodorization of the textile.
[0026] Example 1; (1) β-cyclodextrin and 35 wt% ethanol aqueous solution were mixed, heated to 50°C, stirred at 70 rpm for 20 min, tert-butylhydroquinone was added, heated to 55°C, ultrasonicated at 21 kHz for 2 h, cooled to 2°C, allowed to stand for 20 h, filtered, solid was taken, washed once with anhydrous ethanol, and dried at 50°C for 2 h to obtain inclusion compound A; the mass ratio of β-cyclodextrin, 35 wt% ethanol aqueous solution and tert-butylhydroquinone was 1:100:1;
[0027] (2) Mix seaweed charcoal, cerium oxide, manganese dioxide and opal in a mass ratio of 30:1:5:20 to obtain nano anion powder; mix inclusion complex A, nano anion powder, polyvinyl pyrrolidone and deionized water, stir at 500 rpm for 1 hour, add sodium cellulose, continue stirring for 2 hours, let stand for 24 hours, and then spin. The process parameters are as follows: needle diameter is 1 mm, receiving distance is 22 cm, speed is 50 m / min, and a composite fiber membrane with a thickness of 0.2 mm is obtained; the mass ratio of inclusion complex A, nano anion powder, polyvinyl pyrrolidone, deionized water and sodium cellulose is 1:0.5:0.1:20:2;
[0028] (3) The composite fiber membrane is compounded between two layers of cotton fabric using a polyurethane adhesive. The weight of the cotton fabric is 130g / m 2 , coating amount is 8g / m 2 , a 10 μm thick polyurethane silica is coated on one side of the cotton fabric, the weight ratio of water-based polyurethane resin, nano-silica, cuprous sulfate, KH550 coupling agent and water in the polyurethane silica is 50:8:1:4:80, and the fabric is treated at a pressure of 10 MPa and a microwave power of 750 W for 1 min to obtain a functional multi-layer composite fabric.
[0029] Example 2; (1) β-cyclodextrin and 35 wt% ethanol aqueous solution were mixed, heated to 60°C, stirred at 85 rpm for 30 min, tert-butylhydroquinone was added, heated to 65°C, ultrasonicated at 21 kHz for 3 h, cooled to 5°C, allowed to stand for 25 h, filtered, solid was taken, washed twice with anhydrous ethanol, and dried at 65°C for 3 h to obtain inclusion compound A; the mass ratio of β-cyclodextrin, 35 wt% ethanol aqueous solution and tert-butylhydroquinone was 1.5:100:1.5;
[0030] (2) Mix seaweed charcoal, cerium oxide, manganese dioxide and opal in a mass ratio of 40:2:7.5:40 to obtain nano anion powder; mix inclusion complex A, nano anion powder, polyvinyl pyrrolidone and deionized water, stir at 750 rpm for 2 hours, add sodium cellulose, continue stirring for 3 hours, let stand for 24 hours, and then spin. The process parameters are as follows: needle diameter is 1 mm, receiving distance is 22 cm, speed is 70 m / min, and a composite fiber membrane with a thickness of 0.3 mm is obtained; the mass ratio of inclusion complex A, nano anion powder, polyvinyl pyrrolidone, deionized water and sodium cellulose is 1:0.5:0.3:25:3.5;
[0031] (3) The composite fiber membrane is compounded between two layers of cotton fabric using a polyurethane adhesive. The weight of the cotton fabric is 130g / m 2 , coating amount is 10g / m 2 A 10 μm thick polyurethane silica layer was coated on one side of the cotton fabric. The weight ratio of water-based polyurethane resin, nano-silica, cuprous sulfate, KH550 coupling agent and water in the polyurethane silica layer was 60:11:5:6:90. The fabric was treated for 3 minutes under a pressure of 10 MPa and a microwave power of 870 W to obtain a functional multi-layer composite fabric.
[0032] Example 3; (1) β-cyclodextrin and 35 wt% ethanol aqueous solution were mixed, heated to 70°C, stirred at 100 rpm for 40 min, tert-butylhydroquinone was added, heated to 80°C, ultrasonicated at 21 kHz for 5 h, cooled to 8°C, allowed to stand for 30 h, filtered, solid was taken, washed with anhydrous ethanol 3 times, and dried at 80°C for 5 h to obtain inclusion compound A; the mass ratio of β-cyclodextrin, 35 wt% ethanol aqueous solution and tert-butylhydroquinone was 2:100:2;
[0033] (2) Mix seaweed charcoal, cerium oxide, manganese dioxide and opal in a mass ratio of 50:3:10:50 to obtain nano anion powder; mix inclusion complex A, nano anion powder, polyvinyl pyrrolidone and deionized water, stir at 1000 rpm for 3 hours, add sodium cellulose, continue stirring for 4 hours, let stand for 24 hours, and then spin. The process parameters are as follows: needle diameter is 1 mm, receiving distance is 22 cm, speed is 85 m / min, and a composite fiber membrane with a thickness of 0.5 mm is obtained; the mass ratio of inclusion complex A, nano anion powder, polyvinyl pyrrolidone, deionized water and sodium cellulose is 1:0.5:0.5:30:5;
[0034] (3) The composite fiber membrane is compounded between two layers of cotton fabric using a polyurethane adhesive. The weight of the cotton fabric is 130g / m 2 , coating amount is 15g / m 2, polyurethane silica is coated on one side of the cotton fabric, the weight ratio of water-based polyurethane resin, nano-silica, cuprous sulfate, KH550 coupling agent and water in the polyurethane silica is 70:15:9:8:100, and the fabric is treated for 5 minutes under the conditions of a pressure of 10 MPa and a microwave power of 1000 W to obtain a functional multi-layer composite fabric.
[0035] Comparative Example 1; The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (2) is changed to: seaweed charcoal, cerium oxide, manganese dioxide, and opal are mixed in a mass ratio of 40:2:7.5:40 to obtain nano anion powder; the nano anion powder, polyvinyl pyrrolidone, and deionized water are mixed, stirred at 750rpm for 2h, sodium cellulose is added, and stirring is continued for 3h. After standing for 24h, spinning is carried out, and the process parameters are as follows: the needle diameter is 1mm, the receiving distance is 22cm, and the speed is 70m / min, and the thickness of the composite fiber membrane is 0.3mm; the mass ratio of the nano anion powder, polyvinyl pyrrolidone, deionized water, and sodium cellulose is 0.5:0.3:25:3.5; the remaining steps are the same as Example 2.
[0036] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: mix the inclusion compound A, polyvinyl pyrrolidone and deionized water, stir at 750 rpm for 2 h, add sodium cellulose, continue stirring for 3 h, let stand for 24 h, and then spin. The process parameters are as follows: the needle diameter is 1 mm, the receiving distance is 22 cm, and the speed is 70 m / min. The composite fiber membrane has a thickness of 0.3 mm. The mass ratio of the inclusion compound A, polyvinyl pyrrolidone, deionized water and sodium cellulose is 1:0.3:25:3.5. The remaining steps are the same as Example 2.
[0037] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that there is no step (1), and step (2) is changed to: β-cyclodextrin, polyvinyl pyrrolidone, and deionized water are mixed, stirred at 750 rpm for 2 hours, sodium cellulose is added, and stirring is continued for 3 hours. After standing for 24 hours, spinning is carried out, and its process parameters are: needle diameter is 1 mm, receiving distance is 22 cm, speed is 70 m / min, and the thickness of the composite fiber membrane is 0.3 mm; the mass ratio of β-cyclodextrin, polyvinyl pyrrolidone, deionized water, and sodium cellulose is 1:0.3:25:3.5; the remaining steps are the same as Example 2.
[0038] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (3) is different. Step (3) is changed to: the composite fiber film is compounded between two layers of cotton fabric by a polyurethane adhesive, and the weight of the cotton fabric is 130g / m 2 , coating amount is 10g / m 2, and treated for 3 minutes under the conditions of a pressure of 10 MPa and a microwave power of 870 W to obtain a functional multi-layer composite fabric; the remaining steps are the same as in Example 2.
[0039] Effect example
[0040] Table 1 below shows the performance analysis results of the functional multi-layer composite fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0041] Table 1
[0042] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention uses tert-butylhydroquinone to enter the cavity of the β-cyclodextrin macromolecule through the hydrophobic force, and hydrogen bonds to form an inclusion complex, thereby enhancing the stability of the matrix. Then, the composite β-cyclodextrin is coated with nano-anions, and a fiber membrane is obtained by spinning, which is placed between two layers of cotton fabrics. Under a microwave and high-pressure environment, the upper and lower cotton fabrics are composited as an adhesive, wherein the cyclodextrin and the anion powder work together to adsorb and degrade the odor, so that the fabric achieves a strong deodorization function. Then, the polyurethane silica film coated on the uppermost layer of the fabric forms a three-dimensional silica protective film, which is firmly attached to the cotton fabric, and removes free radicals together with the tert-butylhydroquinone to enhance the antioxidant performance of the fabric.
[0043] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A functional multi-layer composite fabric, characterized in that: The structure of the functional multi-layer composite fabric is cotton fabric-composite fiber membrane-cotton fabric-polyurethane silicon dioxide membrane; The preparation method of the functional multi-layer composite fabric comprises the following preparation steps: β-cyclodextrin and 35 wt% ethanol aqueous solution were mixed, heated to 50-70°C, stirred at 70-100 rpm for 20-40 min, tert-butylhydroquinone was added, heated to 55-80°C, ultrasonicated at 21 kHz for 2-5 h, cooled to 2-8°C, allowed to stand for 20-30 h, filtered, solid was taken, washed with anhydrous ethanol 1-3 times, and dried at 50-80°C for 2-5 h to obtain inclusion compound A; The seaweed charcoal, cerium oxide, manganese dioxide and opal are mixed in a mass ratio of 30-50:1-3:5-10:20-50 to obtain nano anion powder; the inclusion complex A, nano anion powder, polyvinyl pyrrolidone and deionized water are mixed, stirred at 500-1000 rpm for 1-3 hours, sodium cellulose is added, the stirring is continued for 2-4 hours, and after standing for 24 hours, spinning is performed to obtain a composite fiber membrane; The composite fiber membrane is compounded between two layers of cotton fabrics by means of a polyurethane adhesive, the cotton fabric has a gram weight of 130 g / m2, and a coating amount of 8 to 15 g / m2. Polyurethane silica is coated on one side of the cotton fabric, and the fabric is placed in a high-pressure environment at a pressure of 10 MPa and subjected to microwave treatment to obtain a functional multi-layer composite fabric. The weight ratio of the aqueous polyurethane resin, nano-silica, cuprous sulfate, KH550 coupling agent, and water in the polyurethane silica is 50 to 70:8 to 15:1 to 9:4 to 8:80 to 100.
2. A functional multi-layer composite fabric according to claim 1, characterized in that: The mass ratio of the β-cyclodextrin, 35wt% ethanol aqueous solution and tert-butylhydroquinone in step (1) is 1-2:100:1-2.
3. The functional multi-layer composite fabric according to claim 1, characterized in that: The spinning process parameters of step (2) are as follows: needle diameter is 1 mm, receiving distance is 22 cm, and speed is 50-85 m / min.
4. The functional multi-layer composite fabric according to claim 1, characterized in that: The thickness of the composite fiber membrane in step (2) is 0.2 to 0.5 mm.
5. The functional multi-layer composite fabric according to claim 1, characterized in that: In step (2), the mass ratio of the inclusion complex A, nano anion powder, polyvinyl pyrrolidone, deionized water and sodium cellulose is 1:0.5:0.1-0.5:20-30:2-5.
6. The functional multi-layer composite fabric according to claim 1, characterized in that: The thickness of the polyurethane silica in step (3) is 10 μm.
7. The functional multi-layer composite fabric according to claim 1, characterized in that: The process parameters of the microwave treatment in step (3) are: power of 750-1000 W and time of 1-5 min.
Citation Information
Patent Citations
Novel aerogel multifunctional material and preparation method thereof
CN106928908A
Washable negative ion fabric and preparation method thereof
CN115625953A